Arctic Profiles: Second Series - Dickerson, Mark O.; Hills, Len V. (ARCTIC, 1988)
In the June 1982 issue of Arctic, Richard Davis introduced "Arctic Profiles." At the time he said the purpose of the series was to cover "a more subjective and human element that has influenced the history of arctic development." He continued, "Should this series prove successful ." more could follow. . Because of the success of the Profiles, Arctic has decided to maintain the series and has asked us to see it through a second phase. . The second series of profiles will be more contemporary but continue to recognize the contribution of those no longer active or alive. .